Terapia de juego, su incidencia en el comportamiento de los estudiantes de cuarto año de educación básica de la Escuela Juan de Dios, del cantón Quevedo - Intriago Zambrano, Ricardo Fernando (2015)
The behavior of the students have always been present in the classrooms, manifesting themselves in different ways: aggressive, manipulative or rebellious, destructive children, etc. without teachers separating and what to do to prevent or change the specific behaviors that affect others over time if they do not receive adequate and timely attention. These behaviors are evident among the students of the fourth year of the Juan de Dios Zárate school, which is why an investigative process was undertaken in order to end their incidence and establish alternative solutions; based on the results obtained, he was able to establish the best way to counteract these behaviors is through playful activities through play therapies, since many children what they really need is a little love, attention and understanding on the part of teachers and his companions In the absence of an educational counselor in the establishment, these therapeutic games will be directed by the teacher based on a manual of game therapy previously developed for this purpose.